If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -1(3.2) = 3.69 Multiply -1 * 3.2 z + -3.2 = 3.69 Reorder the terms: -3.2 + z = 3.69 Solving -3.2 + z = 3.69 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3.2' to each side of the equation. -3.2 + 3.2 + z = 3.69 + 3.2 Combine like terms: -3.2 + 3.2 = 0.0 0.0 + z = 3.69 + 3.2 z = 3.69 + 3.2 Combine like terms: 3.69 + 3.2 = 6.89 z = 6.89 Simplifying z = 6.89
| 3.5x=3.10 | | 3x+2+45+55=125 | | 3.7=13x+7y | | 4x+(-12)+12=20 | | 0.25=5x-0.25 | | P=4+d | | -4-3y=11 | | 5x+3(x-20)=500 | | 9y+44=2(y+8) | | 4x-8=10+6x | | 44=17x | | 7x-2-2x+7= | | -4+7= | | 3x=12-4 | | 2(4x-3)=6x+10/2x-4 | | =4400[1+0.09(0.25)] | | 4(-1)= | | 3.7x=12 | | -7x-5=-6x-6 | | -2x-3y=-73 | | 5.1=1.7r | | -3(2)= | | 84-3s+s=130 | | -2x-3y=-1 | | 7x-x=-2+4x-3-1 | | y-4x=-2 | | 9/2-8i | | 5y+3X=4 | | =5500[1+0.1(0.75)] | | 15=blog+a | | x-7.4=-4.2 | | 375X=5x-5(3+7) |